Empowering Lay Rescuers in Out-of-Hospital Cardiac Arrest: A Pretest-Posttest Study Guided by Orem’s Self-Care Deficit and Neuman’s Systems Models - Irni Fuzi Wijayanti; Fitriana Kurniasari Solikhah (Inovasi Lokal, 2026)
Introduction: Out-of-hospital cardiac arrest (OHCA) has a low survival rate, making bystander Basic Life Support (BLS) crucial. However, in Indonesia, bystander intervention is frequently hindered by knowledge deficits, cultural norms regarding cross-gender touch, and fear of legal liability. This community service aimed to enhance the BLS competence of PIA Ardhya Garini members as first responders, theoretically grounded in Orem’s Self-Care Deficit and Neuman’s Systems Models. Methods: A quasi-experimental one-group pretest-posttest design was employed involving 60 PIA members. The intervention was a contextualized BLS training integrating legal empowerment (Indonesian Good Samaritan Law), cultural adaptation, and demographic adjustments (Hands-Only CPR for middle-aged women). Effectiveness was evaluated using a validated 10-item cognitive test, and data were analyzed using the Wilcoxon signed-rank test and Normalized Gain (N-Gain). Results: The intervention significantly improved participants' cognitive knowledge. The mean score increased from 6.87 ± 0.96 (pretest) to 9.03 ± 0.74 (posttest) with a p-value < 0.001. The Normalized Gain (N-Gain) was 0.67, indicating moderate effectiveness. The training successfully corrected clinical misconceptions and mitigated specific socio-cultural and legal barriers to bystander intervention. Conclusion: Integrating nursing theories with socio-cultural-legal-clinical modifications effectively empowers laywomen as "dependent care agents" and strengthens community primary prevention against OHCA. To sustain cognitive and psychomotor retention, periodic refresher training every 6–12 months is strongly recommended. This model provides a replicable blueprint for community nursing practice in collectivist societies.